Semantic Analysis of Lexical Relations in College Students Interaction - I Putu Eka Suardana; Ni Nyoman Ayu Tri Hidayanti (UIBU, 2025)
Communication competence is the crucial aspect in communication activities, especially in the college. Therefore, college students must have a sufficient competence in communication including English communication skills. As one of the English communication skills, particulary in Semantics, the ability of using lexical relation is important. Based on that phenomena, this study tries to explore the semantic analysis of lexical relations in college students' interactions to uncover the ways meaning is constructed and conveyed in everyday academic communication. By examining spoken and written exchanges among students, the research focuses on identifying types of lexical relations, including synonymy, antonymy, hyponymy, meronymy, and collocation. The data were collected through recorded group discussions. A qualitative approach was employed to analyze the lexical choices. Findings reveal that students frequently use synonymy and collocation to ensure clarity and fluency in their conversations, while antonymy and hyponymy are used to emphasize contrast and specificity. The study highlights the importance of raising awareness of semantic relationships in language use, especially in academic discourse, to improve communication competence among students. This research contributes to the field of Semantics by providing insights into how lexical relations shape meaning in real life academic interactions and offers implications for language teaching.